Ethnic, socioeconomic and geographical inequalities in road traffic injury rates in the Auckland region. (2nd April 2013) - Hosking, Jamie; Ameratunga, Shanthi; Exeter, Daniel; Stewart, Joanna; Bell, Andrew
Abstract Objective: To describe ethnic, socioeconomic and geographical differences in road traffic injury (RTI) within Auckland, New Zealand's largest city. Methods: We analysed rates of RTI deaths and non‐fatal hospital admissions using the New Zealand Mortality Collection and the National Minimum Data Set 2000–08. Poisson regression examined the association of age, gender, prioritised ethnicity and small area deprivation (New Zealand Index of Deprivation) with RTI rates, and RTI rates were mapped for 21 local board areas within the Auckland region. Results: While RTI rates increased with levels of deprivation in all age groups, the gradient was steepest among children (9% increase/decile) and adults aged 25–64 years (11% increase/decile). In all age groups, RTI risk was highest among Māori. Pacific children had an elevated risk of RTI compared with the NZ European/Other group, but Pacific youth (15–24 years) and adults (25–64 years) had a lower risk. While RTI rates were generally higher for those living in rural local board areas, all but one local board in the southern Auckland urban area had among the highest rates. Conclusions: There are substantial ethnic, socioeconomic and geographic inequalities in RTI risk in the Auckland region, with high rates among Māori (all ages), Pacific children, people living in socioeconomically deprived neighbourhoods, the urban south and rural regions. Implications: To meet the vision of regional plans, road safety efforts must prioritise vulnerable communities at greatest risk of RTI, and implement and monitor the effectiveness of strategies that specifically include a focus on reducing inequalities in RTI rates.